Técnicas grafoplásticas con material reciclable para la motricidad fina en los niños y niñas de 3 años en el centro de desarrollo Domingo Savio periodo septiembre 2013- julio 2014 - Burneo Iñiguez, María Luisa (2015)
The present investigation, called the graph plastic techniques with recycled material to develop the fine motor to the children with 3 years in the center “DOMINGO SAVIO” during the months September 2013 and July 2014 is developed and structured in accordance to the Academic Regimen of the Universidad Nacional de Loja. Researching the theoretical foundation to the graph plastic techniques with recycled material to develop the fine motor to the children with 3 years in the educative center “DOMINGO SAVIO”.Identify the difficulties in the relations with the graph plastic techniques with recycled material to the children with 3 years old in the educative center “.El propósito de las técnicas Grafoplásticas es que los niños mejoraron su motricidad fine through exercises that were performed during the alternative proposal that was It took place at the Center developed DOMINGO SAVIO.The methods used were: Analytical Method, Descriptive Method, Statistical Method and Deductive Method; The techniques used were: Poll applied to the teacher of the educative center “Domingo Savio’. The test educational psychology achievements applied to the initial level children and the observation file, They allowed diagnose the problems with the children and then evaluate the activity Program of techniques Graph Plastic. The principal results of the investigation can describe that the proposal applied to solve the problems was very effective, the activities helped to reduce the difficulties that the children had about the Graph Techniques, moreover the activities applied motivated to the teacher to put in practice in the teach and learn process and this way get good learns to the children.